MINIMASI WASTE DENGAN LEAN MANUFACTURING PADA PRODUKSI TAHU - Rezki Amelia Aminuddin A.P; Zatrian Perdana (PROSIDING, 2022)
CV.Hasan Basri is one of the tofu industries that still have some waste. The purpose of this study is to identify the type of waste and its causes that occur in the tofu production flow, show the priority of improvements that will be carried out based on the results of waste elimination that occurs, and design value stream mapping futures by reducing non-value added activities as proposed improvements. The research method used is Lean manufacturing with value stream mapping (VALSAT) tools. The results showed that in VALSAT the proposed process of sorting and proses of cutting printing is a process that is reduced to curate waste process and over-production. The cycle time in the actual VALSAT is 7258 minutes with a value-added of 770 minutes while after using VALSAT the proposal becomes 7212 minutes with a value-added of 408 minutes in one production cycle time is due to the design of tofu printing tools. Recommendations for improvement to minimize cycle time are layouts and designing tofu printing tools so that the production process is more effective and efficient to minimize waste. Keywords: Lean Manufacturing, Value Stream Mapping, Waste, Tofu production